2014
DOI: 10.1017/s0014479714000313
|View full text |Cite
|
Sign up to set email alerts
|

Soil Properties and Agronomic Performance of Watermelon Grown in Different Tillage and Cover Crops in the South Eastern of Brazil

Abstract: Much of the watermelon (Citullus lanatus) cultivation in Brazil is conducted in sandy soil and topographic conditions that favour the erosion process. Therefore, conservation tillage methods are critical for the sustainability of the production chain of this vegetable crop. We studied different tillage methods and cover crops in watermelon cultivation in the area of the reform of degraded pasture. For this purpose, two tillage methods were established as experimental treatments: minimum tillage preparation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…They concluded that the no-tillage system provided higher yield than the conventional tillage. Branco et al (2014) compared watermelon cultivated on clover and oat straw under minimum tillage and notillage conditions, and observed that root development was restricted in the no-tillage system. However, commercial yield was similar between the treatments (27.4 Mg ha -1 ), except for no-tillage using oat straw Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the no-tillage system provided higher yield than the conventional tillage. Branco et al (2014) compared watermelon cultivated on clover and oat straw under minimum tillage and notillage conditions, and observed that root development was restricted in the no-tillage system. However, commercial yield was similar between the treatments (27.4 Mg ha -1 ), except for no-tillage using oat straw Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Watermelon is one of the main cucurbits cultivated in Brazil; it is planted in a 94,375 ha area, and its yield is 2,171,448 Mg per year (FAO, 2014). Watermelon is grown in the state of São Paulo, primarily in sandy soils (Branco et al, 2014), in degraded pasture lands. Watermelon cultivation requires N as one of the most important nutrients whose deficiency limits this crop productivity (Grangeiro & Cecílio Filho, 2004;Leão et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The use of mulch is considered beneficial for conserving soil moisture, eliminating weeds, and subsequently increasing the nutrient supply to the soil through plant decomposition [8,11,28,29]. In tomatoes, cover crops (e.g., pearl millet and sunn hemp) improve fruit quality and suppress weed growth during plant cultivation [28].…”
Section: Soil Cover and Fruit Yieldmentioning
confidence: 99%
“…The use of mulch is considered beneficial for conserving soil moisture, eliminating weeds, and subsequently increasing the nutrient supply to the soil through plant decomposition [8,11,28,29]. In tomatoes, cover crops (e.g., pearl millet and sunn hemp) improve fruit quality and suppress weed growth during plant cultivation [28]. Mulching with organic material (rice straw, grass clippings, and sawdust) is an accepted practice for many agricultural crops owing to its ability to conserve soil moisture and temperature, control a wide variety of weeds, prevent disease in crops, and improve soil fertility by increasing the organic matter content, in addition to being a repellent of different harmful insects [29].…”
Section: Soil Cover and Fruit Yieldmentioning
confidence: 99%
“…Em contraste, os estudos sobre a ciclagem de raízes finas em florestas tropicais ainda são escassos, e raros estudos utilizando MR podem ser encontrados (GRAEFE et al, 2008a;2008b). Até o momento no Brasil foram desenvolvidos dois estudos com raízes finas utilizando MR BRANCO et al, 2015). Apesar das metodologias para estudar processos subterrâneos terem melhorado significativamente, os estudos de raízes são normalmente realizados nos horizontes superficiais do solo (MAEGHT et al, 2013), e continuam sendo desafios para a biogeoquímica terrestre (VOGT et al, 1993;1996;RYSER, 2006), principalmente em florestas tropicais.…”
Section: Ofereçounclassified